Pengembangan Sistem Aplikasi Percetakan pada PT. Zona Sangangiti Grafika - Teguh Surya; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Zona Sangangiti Grafika is one of the companies engaged in printing that located in Pekanbaru city. This company provides services to produce various kinds of prints such as books, calendars, banners, and others. However, this company has some problems. On the internal side, the application system that is used has not been integrated between each division that can make difference of data between divisions. Besides, order overdue is also a problem. On the external side, customers are not involved in the system so ordering and monitoring process will be difficult. In this study, an application system is developed with some features that are expected to solve the problem. A web-based system developed using the PHP programming language and MySQL database. This research produces a system that integrates all divisions using a database. In addition, the system also provides messaging features, scheduling, and order monitoring. For scheduling, the system uses one scheduling methods namely shortest job first. This methods used for making the schedule created can handle some of the conditions that may occur. After testing, all features run well without any problems.